INSPECTABILITY AND CONTROLLABILITY IN DETERMINED DYNAMIC SYSTEMS OVER FINITE FIELDS - G.I. BELIAVSKIY; A.V. CHERNOV (Advanced Engineering Research)
On the basis of linear control equation the inspectability property of determined dynamic systems over finite fields has been offered. Connection between inspectability and fundamental property of controllability of system is established. The synthesis example of the inspectable determined dynamic system over finite field has been constructed.